PORTOFOLIO MARKOWITZ: UJI OPTIMAL HOLDING PERIOD DAN KINERJA PORTOFOLIO BERDASARKAN KRITERIA RISIKO DAN TARGET RETURN - Andi Ivand Markemo Boangmanalu; Puput Tri Komalasari (Jurnal Manajemen Indonesia, 2015)
The concept of mean-variance optimization, developed by Markowitz, is the cornerstone of modern finance theory. The objective of this portfolio construction is to minimize investment risk by forming optimal portfolios. Dynamic movement in capital markets requires not only changes in portfolio composition. Optimal portfolio is not only determined by the covariance between securities in the portfolio, but also by holding period. The aims of this study is to answer two research questions. The first research question is how long the optimal holding period that was resulted from trade-off between risk and return. This study using target return that are determined hypothetically as well as the risk criteria are divided into 3 namely the mean variance, semivarians and expected loss. Target returns are simulated in this study were divided into 3 criteria namely aggressive, moderate and conservative. The second research question is whether there are differences among the various portfolio performance based on criteria of risk and target return. Portfolio performance is measured by using excess return and the Sharpe index. In this study, stocks covered in LQ-45 index are used to construct efficient portoflio. Monthly price series for company and LQ-45 index for February 2004 to September 2008 are collected. The analysis found that optimal holing period is ranges between 1-5 months. Holding period of a portfolio that more than 5 months will provide risk and return trade-off less favorable. In addition this study found that there was no significant differences in portfolio performance based on overall scenarios